Perfectionnement des conditions du confort par l’isolation et l’amélioration de la compacité volumique du bâti (El-Wahat Journal for Research and Studies, 2017)
This article presents a study on the influence of the compactness on the temperature and humidity as function of the thermal insulation level. The objective is to determine the optimum shape of the building envelope according to the humidex comfort index value. By a modelling approach, already validated and developed under a simulation environment "MATLAB", we were able to offer the possibility of varying the maximumof parameters and thermal properties with regard to the seasonal variations of the external climaticenvironment. The simulation results give an overall idea of these main passive control strategies that improve the conditions of indoor thermal comfort. We have proven that the overall level of thermal insulation required can be lowered if the compactness is in the vicinity of the optimum level.Mots clés : Temperature, Relative humidity, Thermal insulation, Numerical simulation, Thermal comfort.